Boganmeldelser - Henrik Dahl; Peter Garde; Lars Bo Langsted; Beth Grothe Nielsen; Kauko Aromaa; Sysette Vinding Kruse; Ole Scharf; Hans Henrik Brydensholt (Nordisk Tidsskrift for Kriminalvidenskab)
Book reviews